Calcareous Nannofossil adaptations and life-strategies during Oceanic Anoxic Event 2: go dwarf, don't die - G. Faucher; E. Erba (2013)
The environmental changes associated with anthropogenic CO2 emissions will greatly influence the ecosystem functioning of future oceans: the oceans take up anthropogenic-atmospheric CO2 with the consequence of a strong reduction in carbonate ion concentrations leading to ocean acidification. In this scenario, international research is facing the considerable challenge to predict if and how the oceans will be able to respond/adapt to the rapid environmental change and particularly to the acidification of surface waters. The Earth has already experienced extreme environmental change and the geological record shows that one of the most pronounced perturbations of the Cretaceous is the so-called Cenomanian-Turonian Oceanic Anoxic Event 2 (OAE2). OAE2 induced major changes in the marine environment and severe disturbances of the biosphere. The forcing functions behind such phenomena are still problematic: it has been hypothesis that abnormal volcanism triggered global warming and enhanced primary productivity with consequent oxygen consumption at global scale. OAE2 is thought to be linked to the emplacement of the Caribbean Plateau that acted as a natural source of CO2. The environmental perturbation recorded during OAE2 models with 4 main steps: 1. OAE2 onset correlates with a major volcanic episode, causing global warming and a rise in CO2. 2. Then a weathering spike, followed by a cooling episode and CO2 drop in the interval of δ13C peak A, under persisting volcanic emissions. 3. At δ13C peak B, a major volcanic activity is associated with an increase in pCO2. 4. The end of OAE2 is marked by the decrease of carbon isotopic values after δ13C peak C although temperatures remain relative warm. Calcareous nannoplankton, as primary producers, influence the marine carbon cycle and, indirectly, the climate system: they contribute to biological processes, such as photosynthesis and to biomineralization; furthermore nannoplankton are sensitive to chemical - physical - trophic parameters providing the potential for ...